Effects of COVID-19 pandemic on the management of pulmonary hypertension. (January 2023) - Zhou, Christine Y.; Sahay, Sandeep; Shlobin, Oksana; Soto, Francisco J.; Mathai, Stephen C.; Melendres-Groves, Lana; Mullin, Christopher J.; Levine, Deborah J.; Kay, Dana; Highland, Kristin; Bossone, Eduardo; Poms, Abby; et al.
Abstract: The coronavirus of 2019 (COVID-19) disrupted delivery of healthcare. Patients with pulmonary hypertension (PH), especially pulmonary arterial hypertension (PAH), require significant resources for both diagnosis and management and are at high risk for decompensation due to disruption in their care. A survey consisting of 47 questions related to the care of patients with PH was designed by the American College of Chest Physicians 2020–2021 Pulmonary Vascular Disease (PVD) NetWork Steering Committee and sent to all members of the PVD NetWork, as well as the multiple other professional networks for PH. Participation was voluntary and anonymous. Responses were collected from November 2020 through February 2021. Ninety-five providers responded to this survey. The majority (93%) believe that care of PH patients has been affected by the pandemic. Sixty-seven percent observed decreased referrals for PH evaluation. Prior to the pandemic, only 15% used telemedicine for management of PH patients compared to 84% during the pandemic. Telemedicine was used most for follow up of selected low-risk patients (49%). While 22% respondents were completely willing to prescribe new PAH therapy via telemedicine, 11% respondents were completely unwilling. Comfort levels differed based on type of medication being prescribed. Over 90% of providers experienced disruptions in obtaining testing and 31% experienced disruptions in renewal or approval of medications. Overall, providers perceived that the COVID-19 pandemic caused significant disruption of care for PH patients. Telemedicine utilization increased but was used mostly in low-risk patients. Some providers had a decreased level of comfort prescribing PAH therapy via telemedicine encounters.